The Use of Subtitled Video Implemented In Teaching Listening Comprehension at Higher Education During Pandemic: Students' Perception (RETAIN, 2023)
This study aims to describe the application, students' perceptions and understanding towards listening to video material with or without subtitles. The participants in this study were 25 students who are taking online listening courses in their second semester at one of the universities in Surabaya. In collecting the data, the researcher used a qualitative method through learning observations using field notes and open-ended questions interviews with seven students by applying transcript data. The analysis of the data used familiarizing and organizing, coding and reducing, and interpreting and representing. The results showed that students were more likely to understand the material by using subtitles. This result is proven by the average test score of the students is 89/100 points, with the median stepping is 89/100 points and scores ranging is 69-97 points. The result of the interviews conducted with seven students, five students still referred to subtitles, and two others were able to use subtitles wisely. From the result, it can be seen that, in listening to the video, students conduct an analysis at the beginning to understand what the speaker is saying. If they think the audio material is difficult, students will prefer to use subtitles. Meanwhile, some other students chose not to use subtitles because they wanted to improve their English skills.